IMPROVING COMMUNITY ECONOMIC INDEPENDENCE THROUGH MSME PRODUCT DEVELOPMENT IN PADALUYU VILLAGE, CIANJUR REGENCY - Br Ginting, Novita; Hartono, Rudi; Mujahidin, Endin; Rosyadi, Rahmat (LPPM Univ. Ibn Khaldun Bogor, 2023)
To help the Cianjur district affected by the earthquake on November 21, the Directorate General of Higher Education, Research, and Technology (Ditjen Diktiristek) launched the Kampung Cekattan program (Fast, Responsive, Collaborative to Rise and Tangguh Bersama) two programs that are integrated into this program are community self-reliance activities (KKM) and kampung bangkit (KKB) activities. UIKA Bogor participates in community self-reliance activities (KKM) and kampung bangkit (KKB) activities. One of UIKA Bogor's programs is to increase the development of MSME (Micro, Small, and Medium Enterprises) products through activities to increase community economic independence through the development of MSME products in Padaluyu Village, Cugenang District, Cianjur Regency. MSMEs are assisted by as many as 3 (three) MSMEs, namely convection, dry snack culinary, and bamboo woven handicrafts. UIKA Bogor donated equipment, materials, and training to MSME actors as many as 25 packages. The purpose of this activity is to provide solutions for MSME actors affected by the earthquake to restart their businesses and be able to meet the economic needs of families so that they can be economically independent after the earthquake. The implementation team of KKM activities also ensures that the production equipment and materials submitted to MSMEs function and are used by the receiving MSMEs. Based on the results of the monitoring carried out, MSMEs in the fields of bamboo matting, culinary/street vendors, and making snack chips have used and utilized the materials and tools they have received and have returned to activities and have been able to meet the needs of their families again.